Obstetric anal sphincter injuries—Maternal, fetal and sociodemographic risk factors: A retrospective register‐based study. (3rd August 2022) - André, Kristin; Stuart, Andrea; Källén, Karin
Abstract: Introduction: Obstetric anal sphincter injuries (OASIS) are severe complications to vaginal births with potentially serious long‐term consequences and large impact on quality of life. The aim was to determine risk and protective factors for OASIS. Material and methods: We performed a retrospective register‐based observational study. A cohort of 988 988 singleton term deliveries 2005–2016 in Sweden were included. Data from the Swedish Medical Birth Registry and Statistics Sweden were extracted to identify cases of OASIS and maternal and fetal characteristics. Modified Poisson Regression analyses were performed to assess risk factors. Results: The rate of OASIS was 3.5% ( n = 34 583). Primiparity (adjusted risk ratio [aRR] 3.13, 95% CI 3.05–3.21), vacuum extraction (aRR 2.79, 95% CI 2.73–2.86), forceps (aRR 4.27, 95% CI 3.86–4.72), and high birthweight (aRR 2.61, 95% CI 2.50–2.72) were associated with a significantly increased risk of OASIS. Increasing maternal age and decreasing maternal height also increased the risk of OASIS. Obesity increased the risk of OASIS (aRR 1.04, 95% CI 1.04–1.08), if fetal birthweight was not adjusted for. Smoking (aRR 0.74, 95% CI 0.70–0.79) and low maternal education (aRR 0.87, 95% CI 0.83–0.92) were associated with a decreased frequency of reported OASIS. Previous cesarean section increased the risk of OASIS (aRR 1.41, 95% CI 1.36–1.47). Conclusions: Primiparity, instrumental delivery, and high birthweight significantly increased the risk of OASIS. Obesity, low height, increasing age, and previous cesarean section also increased the risk whereas smoking and low maternal educational level were associated with a lower OASIS rate. Abstract :